Avaliação da atividade imunológica In vitro de Alchornea ssp quanto à produção de peróxido de hidrogênio, óxido nítrico e fator de necrose tumoral-alfa por macrófagos murinos - Lopes, Flávia Cristine Mascia [UNESP] (2004)
The use of natural resources as treatment and healing for diseases is as old as the human species. However, most of all plant species were not investigated chemistry or biologically. Many plants used in the traditional medicine modulate the immunological response. The immune system is a remarkably adaptive defense system that has evolved in vertebrates to protect them from invading pathogenic microorganisms and cancer. Macrophages play an important role in this system because they are cells capable to secrete many biological active products such as reactive nitrogen and oxygen species and cytokines. In this work, methanolic extract and ethyl acetate fraction obtained from Alchornea triplinervia and Alchornea glandulosa were studied in the murine immune system using peritoneal macrophages cultures from Swiss mice. Cell viability assays were realized to assure the experimental development. Hydrogen peroxide (H2O2) and nitric oxide (NO) were determined by espectrophotometric procedures and enzyme-linked immunosorbent assay (ELISA) was used to detect tumor necrosis factor (TNF-α) The ability of methanolic extract and ethyl acetate fraction to stimulate or inhibit the murine immune system was evaluated. These plants didn't show immunostimulating properties, once liberation of H2O2, NO and TNF-α were not observed. However, extracts and fractions from both plants, strongly inhibited NO and H2O2 production induced by LPS and PMA, respectively. Production of TNF-α by LPS-stimulated macrophages was partially inhibited. The concentration of 15,62αg/mL from A. triplinervia methanolic extract (cellular viability > 95%) showed to inhibit 88,35% of H2O2, 52,54% of NO and 10,41% of TNF-α production. The ethyl acetate fraction of the same plant and concentration (cellular viability > 90%), inhibited 72,25% of H2O2, 47,80% of NO and 16,41% of TNF-α production. Regarding the A. glandulosa methanolic extract...(Complete abstract click electronic access below)